PEMBELAJARAN HIBRIDA SEBAGAI STRATEGI MODEL PEMBELAJARAN MASA DEPAN - Indra, Noor (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
"Hybrid learning is an effort made by the experts of learning in order to anticipate the phenomenon of JCT development in the community. Where is the growing trend of online learning while on the other hand learning experts also argue that human touch in a process of learning I instruction cannot be separated. Because of the psychological aspects of human needs a certain form of guidance .from the people whom he considers competent. Hybrid learning activities designed to integrate online learning and face to face so that between each other can be mutually reinforcing, complementary, and support and do not treat online methods as duplication of learning in the classroom as well as an additional course (adds-on)"